The Effect of Cash Dividend, Retained Earnings, and Stock Price of Manufacturing Company Listed In Indonesia Stock Exchange - Farah Margaretha (The Winners, 2015)
This study aims to determine the effect of cash dividends per share, retained earnings per share, earnings per share, and leverage on the stock price of manufacture industry in Indonesia from 2008-2012. Research used secondary data in which the source was obtained indirectly through an intermediary medium or data processed from literatures and reports associated with this research. Independent variables in this study (x) are cash dividends per share, retained earnings per share, earnings per share, and leverage, while the dependent variable (y) is stock price. The samples used were 23 companies with purposive sampling method. The empirical results of this study indicate that cash dividends per share, retained earnings per share, earnings per share, and leverage has significant effect on the stock price. It is therefore the higher stock price will attract investors to invest their money. Hence, companies and investors need to attend cash dividends per share, retained earnings per share, earnings per share, and leverage as factors that affect the increase or decrease of the stock price.